The Impact of Television - William A. Belson (London Crosby Lockwood & son LTD, 1967)
Examines how television has affected the behavior and attitudes of Americans. Includes interviews with TV personalities such as John Chancellor, Dick Cavett, Ed Asner, and media critics John Culkin and Linda Kahn.
Keywords: Television viewers; Television -- Psychological aspects; Television -- Public opinion